Sources of validity evidence in the assessment of perceived motor competence in Brazilian schoolchildren - Cavalcante, Wivianne Abreu; Palma, Bartira Pereira; Feitoza, Anderson Henry Pereira; Peixoto, Evandro Morais; Cattuzzo, Maria Teresa (ABCS Health Sciences, 2023)
Introduction: The judgment a child makes about his/her competence in the motor domain is known as perceived motor competence, a key element in building the child's healthy behavior; a Pictorial Scale of Perceived Movement Skill Competence (PMSC) seems to be a suitable perceived motor competence’s assessment, but its validity needs to be evaluated. Objective: To examine the internal structure, the convergent validity, and the reproducibility of the PMSC. Methods: The sample comprised 187 Brazilian healthy schoolchildren (9.6 years ± 0.8); it was applied to the questionnaires PMSC and the Self-Perception Profile for Children scale. Results: PMSC's confirmatory factor analyses indicated adjustment indexes classified as adequate for a two-factor model; there were satisfactory reliability indices (Cronbach’s alpha: 0.654 and 0.652 for locomotion and object control sub domains, respectively); convergent validity (r=0.41 and r=0.56, p<0.001, for locomotion and object control sub domains, respectively). Conclusion: These results contribute to the accumulation of sources of evidence for the PMSC as a valid tool for perceived motor competence assessment in a local and global context.